BIM’s Role in Indonesia’s Green Buildings: Benefits, Challenges, and Stakeholder Preferences - Irene Roselynda Prabarani; Dewi Larasati; Hanson Endra Kusuma (Institute of Research and Community Outreach, Petra Christian University, Indonesia, 2025)
Green building standards have become mandatory in Indonesia’s construction sector, driving environmental benefits while also adding complexity to the construction process. In response, the adoption of Building Information Modeling (BIM) in green buildings has increased; however, its applications and impact are not yet fully understood within the industry. This study aims to identify the benefits and challenges of BIM in GB projects and analyze their impact on stakeholder interest using a mixed-methods approach. The qualitative phase identified 20 benefits and 19 challenges, followed by a quantitative analysis yielding 3 benefit and four challenge factors. Regression results show that “Improvement of Project Sustainability Performance” and “Ease of Construction Visualization” significantly drive stakeholder interest. These findings reinforce the BIM Fields theory, highlighting that BIM's value extends beyond technology to include critical process and policy elements, aligning well with the GreenBIM Triangle for real-world application. However, further analysis is needed to strengthen the findings and optimize the integration of process and policy considerations to enhance BIM adoption.